CAVALCANTE, Alcilene; XAVIER, Dulce (Orgs.). Em defesa da vida: aborto e direitos humanos. - Porto, Rozeli Maria; Grossi, Miriam Pillar (Revista Estudos Feministas, 2008)
CAVALCANTE, Alcilene; XAVIER, Dulce (Orgs.). Em defesa da vida: abo